Necrotic Enteritis Caused by Clostridium perfringens in Blue and Gold Macaws (Ara ararauna) - De Santi, Mariele [UNESP]; Schocken-Iturrino, Rubén Pablo [UNESP]; Casagrande, Mariana Froner [UNESP]; Boarini, Lívia [UNESP]; De Souza Pollo, Andressa [UNESP]; Werther, Karin [UNESP] (Association of Avian Veterinarians (AAV), 2020)
Clostridium perfringens types A and C, which are gram-positive, anaerobic, spore-forming bacteria, can cause necrotic enteritis in birds. Although Clostridium perfringens is considered a commensal organism in the avian intestinal tract, in association with severe stress, other infectious agents, or immunosuppressive conditions, it can cause disease outbreaks. This report describes a disease occurrence of necrotic enteritis caused by C perfringens in macaws (Ara ararauna). Two adult male blue and gold macaws maintained in a zoo exhibit were presented for postmortem examinations after histories of sudden death. Based on the gross examinations and microscopic evaluation of submitted tissue from both birds, the cause of death was determined to be necrotic enteritis. Microbiologic assays followed by polymerase chain reaction analyses identified the isolated strains as C perfringens type A, indicated by only being positive for the cpa gene that encodes the α-toxin. The birds were maintained in an exhibit in which patrons can interact with the animals within their environment. Thus, organisms, such as this pathogen, may present a danger for other birds because visitors could disperse the bacterium to other parts of the zoo.
Keywords: Ara ararauna; avian; blue and gold macaw; clostridiosis; Clostridium perfringens; endotoxemia; microbiology; molecular assay; psittacine birds; zoo